School dropout and completion international comparative studies in theory and policy - Lamb, Stephen; Markussen, Eifred; Teese, Richard; Polesel, John; Sandberg, Nina (Springer Netherlands, 2011)
School dropout remains a persistent and critical issue in many school systems, so much so that it is sometimes referred to as a crisis. Populations across the globe have come to depend on success at school for establishing careers and gaining access to post-school qualifications. Yet large numbers of young people are excluded from the advantages that successful completion of school brings and as a result are subjected to consequences such as higher likelihood of unemployment, lower earnings, greater dependence on welfare and poorer physical health and well-being. Over recent decades, most western nations have stepped up their efforts to reduce drop out and raise school completion rates while maintaining high standards. How school systems have approached this, and how successful they are, varies. This book compares the various approaches by evaluating their impact on rates of dropout and completion. Case studies of national systems are used to highlight the different approaches including institutional arrangements and the various alternative secondary school programs and their outcomes. The evaluation is based on several key questions: What are the main approaches? How do they work? For whom do they work? And, how successful are they in promoting high rates of completion and equivalent outcomes for all? This book examines the nature of the dropout problem in advanced industrialized countries with the goal of developing a broader, international understanding that can feed into public policy to help improve completion rates worldwide.